E-Agriculture: Montenegro Case (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2015)
The use of information technology in the field of agriculture is one of the biggest challenges in the field of agriculture in economic transition in Montenegro. Montenegrin society has made significant progress in the development of agriculture, but there are difficulties in the implementation of modern technologies in all phases of agricultural production. The importance of ICT application in agriculture is very significant from the standpoint of reductions in manufacturing costs, yield increase, protection of the environment, etc. This paper will deal with the problems and proposed solutions (examples) for the application of ICT in the production process, in the process of planning and reporting within the agricultural sector. The research focuses on a comparison of the current situation in the Montenegrin agricultural sector with the situation at the EU level as well as several global initiatives. ICT application in agriculture is also important from the point of view of producers (small and large), and from the standpoint of the state in terms of monitoring the implementation of planned activities. Therefore, it is crucial for Montenegro to keep developing in this field. This paper could also serve as a guideline for the Government in implementation of development policies in the e-Agriculture field.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.